Soziale Proteste in Israel: die Eroberung neuer sozialer Räume - Eizenberg, Efrat (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2012)
This assay recaps the social struggle in Israel that begun in the summer of 2011. It offers some comparison between praxis and discourse of protest in Israel and some of the other social struggles of 2011. Mainly, this assay captures some of the main coordinates of the social struggle that are unique to the Israeli politico-economic context, namely the effort to constitute a social sphere that is based on economic justice while suppressing the dominant political divide over the Israeli-Palestinian conflict. For this end I will review those methods of building new common grounds, claims that the protest in Israel was able to disseminate, and its achievements so far.